Pengaruh Pay Satisfaction, Supervisor Support, Career Development, Worklife Balance dan Workload Terhadap Job Satisfaction Pegawai di PT PLN (Persero) UID Suluttenggo - Roman Kanta Sting Ruminggo; Zoel Hutabarat (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to determine the influence of Pay Satisfaction, Supervisor Support, Career Development, Worklife Balance and Workload on Job Satisfaction. In this research, the cross-sectional method was used to obtain quantitative data from questionnaires distributed online. The questionnaire was taken and modified based on existing questions from previous literature. Data was obtained from 206 respondents who were members of the population who were organic employees at PT PLN (Persero) UID Suluttenggo using probability sampling techniques. The data was then analyzed using Smart PLS4 software. The research results show that there is a positive relationship between Pay Satisfaction, Supervisor Support, Career Development and Worklife Balance on Job Satisfaction, but Pay Satisfaction does not show a significant relationship. Meanwhile, Workload was found to have a negative effect on Job Satisfaction. The results of this research provide managerial implications that will help companies increase job satisfaction. There are several limitations to this research, so it is followed by recommendations for further research.